Nursing competences used during the qualification of a patient with pressure ulcer for Long-Term Nursing Home Care. - Mucha, Katarzyna (Pielęgniarstwo w Opiece Długoterminowej / Long-Term Care Nursing, 2022)
A home long-term nursing nurse takes direct care of a seriously ill patient by making home visits. the nurse is morally and legally responsible for their medical decisions. This case report describes the eligibility for long-term home care of a patient with extensive pressure ulcer at the end of life. Qualification is done by a Master of Nursing, specialist in palliative care nursing, using the competences acquired in the course of education, as well as skills and experience resulting from many years of professional work. Patients with pressure ulcers, at the end of their lives, very often receive specialist long-term care at home. The main activities are undertaken in the field of treatment and care of chronic, difficult to heal wounds, patient care in accordance with a previously established nursing process, as well as broadly understood education of relatives and actual caregivers. An important role in this process is played by the nurse, whose preparation and professional experience enable independent making medical decisions.